(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Hydronephrosis, a condition that is mostly congenital, is considered as the most common type of pediatric urinary tract disorder. The aim of this study was the evaluation of the prognosis and outcomes of hydronephrosis in cases of congenital hydronephrosis. Methods. In a cross-sectional study, run in a tertiary clinic of pediatric nephrology, from 2015 to 2020, patients with fetal hydronephrosis were selected. Ultrasonography, urinalysis and kidney function tests were ordered for all patients and in the presence of hydronephrosis, repeated ultrasonography, voiding cystourethrography and dimercaptosuccinic acid scan were performed. In cases with evidence of obstruction, a diethylenetriamine pentaacetic acid scan and relative surgical procedures were performed. Results. Among 141 cases, mean age was 8 ± 1.4 years and 80.9% were male. Partial or complete obstruction in the right and left kidney was found in 16.3 and 24.8% of patients, respectively. The degree of hydronephrosis was mild in 46.1%, moderate in 39%, and severe in 9.2% of the patients. At the last follow-up period, hydronephrosis recovered in 46% of the patients, while 54% experienced persistence or exacerbation of the disease. Meanwhile, 7.1% of patients showed neurogenic bladder, 19.1% urinary tract infection and 22.7% urinary stones. Conclusion. Our study revealed that fetal hydronephrosis ends in complete recovery following birth in 46% of the cases. However, in cases experiencing persistent or exacerbating hydronephrosis, optimized treatment and/or surgical intervention are required. DOI: 10.52547/ijkd.6516